Standortpräferenzen, intraregionale Wanderungen und Verkehrsverhalten: Ergebnisse einer Haushaltsbefragung in der Region Dresden - Bauer, Uta; Holz-Rau, Christian; Scheiner, Joachim (Raumforschung und Raumordnung | Spatial Research and Planning, 2005)
The contribution focuses on the dependence of intra-regional migration behaviour of private households from their migration motives, housing needs and locational requirements, as well as on interdependencies between locational decisions and individual travel behaviour. The results are based on a household survey carried out in the region of Dresden, which is put in context with empiricial results of other studies. The results show that migrations correspond with the housing requirements and locational preferences of the respective household, but they are also influenced by external conditions. As a consequence, locational behaviour affects mode choice and activity spaces of the household members, but in turn, locational behaviour itself is influenced by household motorization. The contribution concludes with some considerations on the compatibility of the locational preferences of private households and individuals with the guiding principle of compact settlement structures.